A Comparative Analysis of The Conceptions of Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi in Islamization of Knowledge - Solihah binti Haji Yahya Zikri (Dirosat : Journal of Islamic Studies, 2017)
There has been a lot of discussion and debate on the issues of Islamization of Contemporary Knowledge among Muslim intellectuals. Two Muslim thinkers namely al-Attas and al-Faruqi were foremost in the attempt to conceptualize the problem of the Muslim Ummah and the issue of Islamization of knowledge as an epistemological and socio-political solution. This article aims to examine, compare and analyze the ideas of both scholars with respect to the various interpretations of the concept of Islamization of knowledge their definition of the concept, their philosophical framework, and their methodology for achieving the goals of Islamization. It aims at understanding the similarities and differences and the strengths and weaknesses of their conceptions, philosophical framework and methodology. This paper also explores the possibility of reconciliation between their ideas in the hope of further advancing the cause of Islamization of knowledge.